Hypercholesterolemia 2015
DOI: 10.5772/59491
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Studies of ACE Inhibitors with Statins

Abstract: Hypercholesterolemia 204 tissue distribution. All ACE inhibitors have a similar antihypertensive efficacy -they effectively block the conversion of angiotensin 1 to angiotensin II -and all have similar therapeutic indications, adverse effect profiles and contraindications. Mechanism of actionThese inhibitors block the converting enzyme of angiotensin, which is responsible for cleavage from angiotensin I, which is decapeptide, to angiotensin II, which is octapeptide [17,18], and lower the BP by reducing PVR (pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Hans Brunner and John Laragh [6] administered it to hypertensive patients and showed that it was extremely effective in lowering blood pressure. The structural requirements for substrates of angiotensin converting enzyme to cleave a substrate are found similar to those observed with carboxypeptidase A of bovine pancrease [7,8]. The substrate specificity and other properties of angiotensin converting enzyme suggested that it was a zinc metallopeptidase, similar in mechanism to carboxypeptidase A, an enzyme whose active site had been well characterized by x-ray crystallography and other methods [9].…”
Section: Introduction 11 Angiotensin Converting Enzymementioning
confidence: 54%
“…Hans Brunner and John Laragh [6] administered it to hypertensive patients and showed that it was extremely effective in lowering blood pressure. The structural requirements for substrates of angiotensin converting enzyme to cleave a substrate are found similar to those observed with carboxypeptidase A of bovine pancrease [7,8]. The substrate specificity and other properties of angiotensin converting enzyme suggested that it was a zinc metallopeptidase, similar in mechanism to carboxypeptidase A, an enzyme whose active site had been well characterized by x-ray crystallography and other methods [9].…”
Section: Introduction 11 Angiotensin Converting Enzymementioning
confidence: 54%
“…Atorvastatin and lisinopril are a successful combination for the treatment of patients with chronic heart failure and hypertension (Naveed 2015;GoodRx undated). Analytical methods of analysis (Leis et al 1998(Leis et al , 1999El Gindy et al 2001;Andreas et al 2003;El-Emam et al 2004;Beasley et al 2005;Rahman et al 2005aRahman et al , 2005bHuang et al 2006;Stanisz and Kania 2006;Chaudhari et al 2007;Ivanovic et al 2007;Shah et al 2007;Basavaiah et al 2009;Chauhan et al 2011;Jamakhandi et al 2011;Sultana et al 2011;Kumar et al 2012;Naveed et al 2012;Arayne et al 2013;Hafez et al 2014;Lakshmi and Sreedevi 2014;Sathiyasundar and Valliappan 2014;Sbârcea et al 2014;Shulyak et al 2021aShulyak et al , 2021bShulyak et al , 2021c have been developed for the determination of atorvastatin and lisinopril in medicines and biological liquids.…”
Section: Introductionmentioning
confidence: 99%